Effects of Microplastic on the Population Dynamics of a Marine Copepod: Insights from a Laboratory Experiment and a Mechanistic Model. (9th June 2022) - Everaert, Gert; Vlaeminck, Karel; Vandegehuchte, Michiel B.; Janssen, Colin R.
Abstract: Microplastic is ubiquitously and persistently present in the marine environment, but knowledge of its population‐level effects is limited. In the present study, to quantify the potential theoretical population effect of microplastic, a two‐step approach was followed. First, the impact of microplastic (polyethylene, 0.995 g cm −3, diameter 10–45 µm) on the filtration rate of the pelagic copepod Temora longicornis was investigated under laboratory conditions. It was found that the filtration rate decreased at increasing microplastic concentrations and followed a concentration–response relationship but that at microplastic concentrations <100 particles L −1 the filtration rate was not affected. From the concentration–response relationship between the microplastic concentrations and the individual filtration rate a median effect concentration of the individual filtration rate (48 h) of 1956 ± 311 particles L −1 was found. In a second step, the dynamics of a T. longicornis population were simulated for realistic environmental conditions, and the effects of microplastics on the population density equilibrium were assessed. The empirical filtration rate data were incorporated in an individual‐based model implementation of the dynamic energy budget theory to deduct potential theoretical population‐level effects. The yearly averaged concentration at which the population equilibrium density would decrease by 50% was 593 ± 376 particles L −1 . The theoretical effect concentrations at the population level were 4‐fold lower than effect concentrations at the individual level. However, the theoretical effect concentrations at the population level remain 3–5 orders of magnitude higher than ambient microplastic concentrations. Because the present experiment was short‐term laboratory‐based and the results were only indirectly validated with field data, the in situ implications of microplastic pollution for the dynamics of zooplankton field populations remain to be further investigated. Environ Toxicol Chem 2022;41:1663–1674. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.